Identification of two novel alleles, HLA‐A*02:01:193 and ‐DQA1*02:17, in Greek individuals. (1st March 2021) - Zamanakou, Maria; Vatsiou, Sophia; Stokidis, Savvas; Fortis, Sotirios P.; Germenis, Anastasios E.
Abstract : Identification by NGS of two novel alleles, HLA‐A*02:01:193 and ‐DQA1*02:17, in Greek individuals.